Identification Of Seagrass Ecosystems In Teluk Bakau Village Gunung Kijang District, Bintan Regency - Bestari, Indah; Eddiwan, Eddiwan; Efizon, Deni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract This research was conducted in March 2019, located in the village of Teluk Bakau, Gunung Kijang District, Bintan Regency. Sampling was carried out in 3 sampling areas, with 3 replications over one month. The purpose of this study was to identify the type of gastropods that live in seagrass ecosystems. This research uses survey method, with line transect technique. The results of the study found 15 species from the Gastropod group that live in seagrass ecosystems, namely: Trochus niloticus, Conus amadis, Murex troscheli, Colubraria soverbii, Hemifusus colosseus, Strombus urceus, Cypraea auratium, Bullia mauritiana, Nassicus reticulate, Tonna cepa papilla Volema paradisiacal, Solenostreira pallida. Based on the measurement results of Gastropods living habitat conditions were recorded: temperature (29-300C), transparency (105-109.5 cm), salinity (33-34‰), acidity (8), dissolved oxygen (2.02-5.52 mg/L), and substrate with gravel and muddy sand. Keywords:Seagrass ecosystems,Gastropoda, line transects, living habitats